A Technology Survey on IoT Applications Serving Umrah and Hajj. (12th August 2022) - Binsawad, Muhammad; Albahar, Marwan
Abstract : Emerging technologies provide a highly compatible platform for analyzing substantial data volumes relating to crowd management. These technologies are not only effective in providing remedial solutions but they are also cutting-edge, saving both time and money, and user-friendly. About twenty percent of the world's Muslims are granted the ability to take part in religious observances on an annual basis. An in-depth analysis of the technologies and applications used in the Hajj and Umrah systems is required given the importance of utilizing and adapting technology to assist pilgrims performing the Hajj and Umrah. Both of these pilgrimages are considered acts of worship by Muslims. As a result, the services provided during Umrah and Hajj will be significantly enhanced if the numerous technological advancements that are evaluated in this paper are implemented. The majority of previous research is shown to revolve around artificial intelligence and embedded Internet of Things technologies in the paper, highlighting a gap in the research that should be filled by investigating the necessity of discussing and introducing immersive technologies. During the annual pilgrimage to Makkah, Saudi Arabia, several different technologies are utilized with the goal of enhancing the quality of services provided to pilgrims performing the Umrah and Hajj. This paper provides an analysis of these technologies. The findings of this paper point to new research directions as well as a more realistic and practical approach to improving services during Umrah and Hajj.